Resilience, Confidence-Building, and Performance: - Audrey Ricke (Journal of the Scholarship of Teaching and Learning)
Adaptive digital learning courseware is becoming part of the instructor tool kit to support student performance and ultimately reduce DFWI rates. However, past studies of the effectiveness of adaptive digital learning platforms in elevating student performance on summative assessment have shown promising yet at times mixed reviews (e.g. Yarnall et al., 2016). This case study integrates adaptive digital learning to address the challenge of promoting reading and concept application outside of class and analyzes its impacts on students’ engagement in class, perceived learning, and performance on summative assessment. Such an analysis, which considers mediating factors not previously analyzed together in adaptive digital learning studies, such as individual rather than aggregate performance, digital learning platform design differences, resiliency factors, and in-class activities, is an important step in clarifying some of the previously mixed results. Drawing on data collected in two sections of the same general education social science course taught by the same instructor in the same semester, this study illustrates the varying potential of adaptive digital learning to increase student confidence in the material and how it can translate into increased student performance if aligned and coupled in certain ways with in-class active learning. This study also provides evidence that illustrates how digital learning that is designed for greater degrees of editability by faculty can maximize learning benefits for students.